Factors affecting nutrient concentration and stoichiometry of forest trees in Catalonia (NE Spain) - Sardans, J.; Rivas-Ubach, A.; Penuelas, J. (Forest Ecology and Management, 2011)
Although some studies have observed signiﬁcant correlations between latitude and climate gradients and tree leaf nutrient concentration and stoichiometry, others have not. This study examined the nutrient concentrations of tree leaves in 3530 plots of the Catalonian Forest Inventory. Catalonia is a Mediterranean region located in NE Iberian Peninsula. It has a long land-use history and includes the large industrial-urban area of Barcelona but still contains a large forest area (42%). In the forests of Catalonia, leaf nutrient concentration increased and leaf C:nutrient ratios decreased from south to north, which paralleled the increase in MAP (mean annual precipitation) and the decrease in MAT (mean annual temperature), which was expected in a Mediterranean climate where the availability of water is the most limiting factor for plant nutrient uptake. In addition, the availability of water, which inﬂuences productivity, was associated with low leaf N:P content ratios, which is consistent with the Growth Rate Hypothesis. At a regional scale, the results support the Soil-Age Hypothesis because the youngest soils in the Pyrenees had the lowest leaf N:P ratios. Furthermore, the type of forest (evergreen, deciduous, or coniferous) explained some of the variation in leaf nutrient concentrations and stoichiometry. Nutrient concentrations were highest in deciduous trees and lowest in coniferous trees. Leaf nutrient concentrations and stoichiometry were mainly correlated with climate, but other factors such as the chemical properties of soil and rock, phylogenetics, and different ecological histories and anthropogenic factors such as pollution, had an effect.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: ecological stoichiometry; forest climate influence; mediterranean forest; Tree nutrient relationships

Oak trees and soil interactions in Mediterranean forests: a positive feedback model - Aponte, Cristina; García, Luis V.; Pérez-Ramos, Ignacio M.; Gutiérrez, Eduardo; Marañón, Teodoro (Journal of Vegetation Science, 2011)
Questions: What is the spectrum of variability of chemical elements in a Mediterranean forest ecosystem across the different compartments? Do coexisting tree species with different leaf chemical composition and nutrient cycling distinctly modify soil conditions? Could these species-speciﬁc, treegenerated soil changes create a potential positive feedback by affecting longterm species distribution? Location: Mixed oak forests of southern Spain, Los Alcornocales Natural Park. Methods: We sampled and chemically analysed ﬁve different ecosystem components: leaves, leaf fall, litter and superﬁcial (0–25 cm) and sub-superﬁcial (25–50 cm) soil beneath the canopies of evergreen Quercus suber and deciduous Q. canariensis trees. We used multiple co-inertia analysis (MCoA) to conjointly analyse the patterns of variability and covariation of eight macro- and micronutrients determined in each of the sampled ecological materials. We implemented a path analysis to investigate alternative causal models of relationships among the chemical properties of the different ecosystem components. Results: Variability in the concentration of chemical elements was related to the nature of their biogeochemical cycles. However, the rank of element concentration was consistent across ecosystem components. Analysis of coinertia (MCoA) revealed that there was a common underlying multivariate pattern of nutrient enrichment in the ecosystem, which supported the hypothesis of a separation in biogeochemical niches between the two co-existing oak species, with Q. canariensis having richer plant tissues and more fertile soil directly under each tree than Q. suber. The feasibility of a potential tree–soil positive feedback model was the only statistically validated among several alternative (non-feedback) models tested. Conclusions: In the studied Mediterranean forests, oak species distinctly modify soil fertility conditions through different nutrient return pathways. Further investigation is needed to address whether these tree-generated soil changes could affect seedling establishment and ultimately inﬂuence species distribution.
Keywords: Biogeochemical niche; ecological stoichiometry; ecosystem functioning; Foliar analysis; nutrient cycling; Quercus canariensis; Quercus suber; Soil fertility